A Critical Study of Matthew 18:15-18 in New Testament Greek and Selected Akan Mother-Tongue Translations: Implication for Peace-Making in Ghana - Emmanuel Foster Asamoah; Ebenezer Tetteh Kpalam (European Scientific Journal, ESJ, 2024)
Recent global research reveals a world characterised by increasing fragmentation, diminished peace, and mounting risks for future generations. Diverse conflicts, ranging from familial to national issues, persist, even among individuals sharing the same faith. In Africa, nations like Cote d’Ivoire, the Democratic Republic of Congo, Burundi, Rwanda, the Central African Republic, and Sierra Leone grapple with severe consequences of conflicts. In Ghana, pockets of ethnic discord impact education, healthcare, and social services, prompting the emigration of skilled professionals. Despite ongoing peace efforts in Ghana, effective approaches are crucial. With over 70% of Ghanaians identifying as Christians, contextualising peace-making within sacred texts becomes imperative. In this exploration, the study delves into a biblical approach, specifically scrutinising Matthew 18:15–18 through exegetical analysis in Greek language and mother-tongue hermeneutics. These approaches reveal a convergence between the biblical author’s original meaning conveyed in the Greek language and its interpretation in the mother tongue. The paper advocates private conflict resolution to avoid gossip, involving witnesses if needed and church leaders if the issue persists. Disciplinary measures may be necessary, emphasising personal dignity and adherence to God’s will. The paper significantly contributes to conflict resolution knowledge, providing valuable insights for fostering peace in Ghana and beyond.